CHANGES IN THE CELLULAR COMPOSITION AND BIOCHEMICAL INDICATORS OF SYNOVIAL FLUID IN CHRONIC SYNOVITIS - Inoyatova F.Kh., Islamova N.U., Karimov M.Yu. (Central Asian Journal of Medicine, 2025)
The article presents the results of a study of the cellular composition and physicochemical properties of synovial fluid (SF) in patients with acute and chronic synovitis of the knee joint. It was found that chronic synovitis is accompanied by more pronounced changes in cellularity and inflammatory markers in the SF compared to the acute process. An analysis of cytological parameters was performed, including the number of leukocytes, erythrocytes, the presence of polynuclear cells, rhagocytes, histiocytes, macrophages and crystals, using a modified formula for the inflammatory activity index. A direct relationship was found between the degree of turbidity of the SF, the number of leukocytes and the severity of degenerative changes in the joint. The data obtained confirm the diagnostic significance of a comprehensive analysis of the SF in assessing the severity of the inflammatory process and predicting the course of chronic synovitis of the knee joint.